The processfolio: a critical action research intervention designed to mitigate negative impacts of writing assessment practices on agency in a UK EAP pre-sessional context - Pearson, Jayne (2019)
This thesis is concerned with the interaction between assessment and agency. The context in which the research took place is an English for Academic Purposes (EAP) department of a UK university, specifically its summer pre-sessional courses which prepare and assess postgraduate international students’ academic language for their degree programmes. The specific focus of this thesis is the negative impacts of academic writing assessment practices within this context on students’ ability to a) exercise agency in learning and assessment situations b) conceptualise themselves as developing writers. The research was underpinned by a critical realist perspective, which allowed educational assessment to be seen as a layer of societal structure with the potential to enable and constrain individual and social agency. An action research methodology in iterative cycles over three consecutive years was employed to investigate and intervene. As a response to the negative impacts identified in a reconnaissance cycle in 2013, I designed and implemented a processfolio assessment for academic writing to facilitate student agency around assessment. The first intervention took place in 2014 with my own class of 14 students; the second in 2015 widened the participation to three classes (46 students) and three teachers including myself. Due to the necessity for flexibility in methods of data collection in this context, a range of methods and analysis was employed in each cycle. Data sets generated through both intervention cycles were the processfolios themselves and interviews with students and teachers. Benefits deriving from the processfolio were that students both demonstrated and reported high levels of self-efficacy and awareness of writing as a both a social practice and an individual metacognitive process. In keeping with the aims of action research underpinned by a critical realist approach to agency, the students showed a growing critical consciousness of the potential of EAP assessment to constrain or enable their understandings of writing, and their relationships with themselves, peers, teachers, and the academy. Participating teachers’ tacit assumptions about assessment practices and EAP writing pedagogies were also disrupted. Moreover, through a reflexive process, my own understanding of the original intention of the processfolio shifted. For practical and philosophical reasons, it should not be a replacement assessment tool to foster better learning behaviours. Rather, I conclude that the processfolio should be used on the pre-sessional to mitigate the negative impacts of assessment by creating conditions for a continuous dialectic between agency and structure. These findings imply that this approach to action research in assessment writing in EAP can contribute to a greater understanding of the mediating conditions which shape assessment practices.